2017
DOI: 10.5152/tud.2017.35488
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted radical perineal prostatectomy: first experience of 15 cases

Abstract: Objective: Minimally invasive techniques are increasingly evolving and preferred to reduce surgical induced morbidity and mortality and minimize the challenges of surgical techniques. Especially radical perineal prostatectomy (RPP) includes some challenges like working in a deep and narrow space and challenging ergonomics for the surgeons. Because of these issues open RPP is still performed in experienced centers. In order to reduce these difficulties, robot-assisted radical perineal prostatectomy (r-RPP) is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…But, he preferred surgical treatment and r-PRP was performed using a Da Vinci XI robotic system (Intuitive Surgical Inc., Sunnyvale, CA, USA) as defined in our article on 15 patients (▶ Fig. 2) [2].…”
Section: Zusammenfassungmentioning
confidence: 99%
See 1 more Smart Citation
“…But, he preferred surgical treatment and r-PRP was performed using a Da Vinci XI robotic system (Intuitive Surgical Inc., Sunnyvale, CA, USA) as defined in our article on 15 patients (▶ Fig. 2) [2].…”
Section: Zusammenfassungmentioning
confidence: 99%
“…Robotic PRP (r-PRP) was first performed by Kaouk et al in a cadaver model and then in 4 living patients [1]. Then, we published our experience on 15 patients who underwent r-PRP [2].Today, penile prosthesis implantation is the gold standard treatment modality with high satisfaction and low complication rates for the medical treatment of refractory erectile dysfunction. It has two types: malleable and inflatable (2-piece, 3-piece).…”
Section: Introductionmentioning
confidence: 99%
“…As this technique is performed below the endopelvic fascia and bladder neck level, anatomy and physiology created by several prior surgeries such as kidney transplantation or intestinal bypass systems for colorectal cancer can be maintained. Tugcu et al performed this technique in 15 patients and reported that it can be safely performed in terms of oncological and functional outcomes (6). In this study, we aimed to investigate the effect of pelvimetric diameters measured preoperatively by multiparametric magnetic resonance imaging on peroperative findings and postoperative oncological outcomes.…”
Section: Introductionmentioning
confidence: 97%
“…Kaouk et al [2,3] described the technique of robot-assisted radical perineal prostatectomy (r-RPP) model on cadavers and reported the results of first four patients. Tugcu et al [4] initially applied this technique to 15 patients and reported that this technique could be applied safely by presenting their results. Based on the results of the patients in the series, it was found that this method provides great advantages in patients with high body mass index, which was a major handicap for prior abdominal surgeries.…”
Section: Introductionmentioning
confidence: 99%